2022
DOI: 10.1038/s41467-022-30641-9
|View full text |Cite
|
Sign up to set email alerts
|

Persister state-directed transitioning and vulnerability in melanoma

Abstract: Melanoma is a highly plastic tumor characterized by dynamic interconversion of different cell identities depending on the biological context. Melanoma cells with high expression of the H3K4 demethylase KDM5B (JARID1B) rest in a slow-cycling, yet reversible persister state. Over time, KDM5Bhigh cells can promote rapid tumor repopulation with equilibrated KDM5B expression heterogeneity. The cellular identity of KDM5Bhigh persister cells has not been studied so far, missing an important cell state-directed treatm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 83 publications
0
20
0
Order By: Relevance
“…Additionally, an acquisition of mesenchymal identity in HER2-amplified breast cancer cells upon treatment with Lapatinib was demonstrated ( Hangauer et al, 2017 ). Following these discoveries, efforts were made to detect and target the vulnerabilities of drug-tolerant cells, in various cancers and treatments ( Hangauer et al, 2017 ; Chauvistré et al, 2022 ). A recently published work identified a unique sub-population of cycling persister cells that can potentially be targeted therapeutically ( Oren et al, 2021 ).…”
Section: Cancer Plasticitymentioning
confidence: 99%
“…Additionally, an acquisition of mesenchymal identity in HER2-amplified breast cancer cells upon treatment with Lapatinib was demonstrated ( Hangauer et al, 2017 ). Following these discoveries, efforts were made to detect and target the vulnerabilities of drug-tolerant cells, in various cancers and treatments ( Hangauer et al, 2017 ; Chauvistré et al, 2022 ). A recently published work identified a unique sub-population of cycling persister cells that can potentially be targeted therapeutically ( Oren et al, 2021 ).…”
Section: Cancer Plasticitymentioning
confidence: 99%
“…Figure b plots the persister cells, which moved throughout the entire 48 h experiment. The persister cell framework is new in cancer biology, adapted from a well-established concept in microbiology. , In this framework, drug-resistant cells in tumors are no longer attributed to metabolic arrest or quiescence but rather persister cells with an innate or adopted aggressive phenotype . The decrease in the number of cells tracked between the all and persister categories is due to arrested movement, loss of signal, or cells moving outside the imaging region.…”
Section: Resultsmentioning
confidence: 99%
“…49,50 In this framework, drug-resistant cells in tumors are no longer attributed to metabolic arrest or quiescence but rather persister cells with an innate or adopted aggressive phenotype. 51 The decrease in the number of cells tracked between the all and persister categories is due to arrested movement, loss of signal, or cells moving outside the imaging region. Both plots show cells invaded a range of distances, with the average cell movement decreasing as distance from the source of oxygen and nutrients increases.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…These KDM5B high subpopulations also contribute to intrinsic multidrug resistance by promoting oxidative phosphorylation and maintaining a high ratio of reduced-to-oxidized glutathione [103,104]. On the other hand, enforced KDM5B expression limits tumor plasticity and heterogeneity, resulting in the elimination of melanoma cells by promoting melanocytic differentiation [105]. The authors of a recent study identified an immune evasion function driven by KDM5B in melanoma [44].…”
Section: Kdm5bmentioning
confidence: 99%